2022
DOI: 10.5194/angeo-40-67-2022
|View full text |Cite
|
Sign up to set email alerts
|

Snow cover variability and trend over the Hindu Kush Himalayan region using MODIS and SRTM data

Abstract: Abstract. Snow cover changes have a direct bearing on the regional and global energy and water cycles and the change in the Earth's climate conditions. We studied the relatively long-term (2000–2017) altitudinal spatiotemporal changes in the coverage of snow and glaciers in one of the world's largest mountainous regions, the Hindu Kush Himalayan (HKH) region, including Tibet, using remote sensing data (5 km grid resolution) from the Moderate Resolution Imaging Spectroradiometer (MODIS) on board the Terra satel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In this regard, seasonal trends of SCA were analyzed between December 2002 and November 2020 at grid scale, which remained understudied so far. Recent studies generally focused on annual trends and study periods until 2017 (Ackroyd et al, 2021;Desinayak et al, 2022) and 2018 (Notarnicola, 2020). In detail, the results of this study pointed towards partially significant decreasing and increasing trends at seasonal scale (Figure 5c), whereas trends at basin scale were mostly insignificant indicating that SCA remained stable (Table 2).…”
Section: Snow Cover Areamentioning
confidence: 62%
“…In this regard, seasonal trends of SCA were analyzed between December 2002 and November 2020 at grid scale, which remained understudied so far. Recent studies generally focused on annual trends and study periods until 2017 (Ackroyd et al, 2021;Desinayak et al, 2022) and 2018 (Notarnicola, 2020). In detail, the results of this study pointed towards partially significant decreasing and increasing trends at seasonal scale (Figure 5c), whereas trends at basin scale were mostly insignificant indicating that SCA remained stable (Table 2).…”
Section: Snow Cover Areamentioning
confidence: 62%
“…The present synthesis shows that procuring a trend in snow cover changes is challenging for the Himalayan region due to the limited number of observations, substantial annual and inter-annual variability, and scarce in-situ snow depth area data (Kulkarni et al, 2021). However, overall, it is widely reported that depleting snow cover and its spatiotemporal changes are associated with changes in climatic variables over the Himalaya (Sood et al, 2020;Desinayak et al, 2022). Understanding variability of snow cover with respect to altitude and air temperature is vital for assessing availability of regional water resources and the impact of climate change in the Himalaya (Immerzeel et al, 2010;Shrestha et al, 2015).…”
Section: Snow Cover Snow Depth and Snow Water Equivalent Variability ...mentioning
confidence: 83%
“…Accurately identifying alterations in snow coverage remains a challenging task due to multiple factors. For example, the rough geography of mountainous regions, the influence of shadow effects, and the ever-changing climatic conditions [35,36]. Change detection plays a crucial role in analysing temporal variations and visually representing diverse changes on a unified map [37].…”
Section: Introductionmentioning
confidence: 99%